Catholic Ethics of War: On the Plausibility of Christian Pacifism - Cebula, Adam (Studies in Christian ethics, 2024)
This article proposes three responses to the anti-war statements made recently by Pope Francis. The first one recapitulates the very foundations of the prevalent legal and ethical approaches to the issue of war—laid by the most influential Christian thinkers of all times, revisited on several occasions by their followers, and ultimately confirmed in the fairly recent documents articulating Catholic war ethics. The second discusses the specific mode of Francis's apparent repudiation of the doctrine of just war, implying the essential equalisation of the moral status of either warring party—even in the case of conflicts initiated and sustained by undeniable and unprovoked acts of aggression. The third examines the reasonableness and moral soundness of the Pope's implied belief in the impermissibility of an attacked political community's (unintendedly) exposing its members to the enemy's violence without having a substantiated prospect of (relatively swift) military success of its defensive undertaking.